Extrinsic pulmonary stenosis in primary mediastinal B‐cellular lymphoma. Issue 1 (22nd January 2014) - Pugliatti, Pietro; Donato, Rocco; Grimaldi, Patrizia; Nunnari, Flavia; de Gregorio, Cesare; Zito, Concetta; Carerj, Scipione
ABSTRACT We describe the case of a 34‐year‐old man with a history of asthenia and excessive fatigability. Transthoracic echocardiography showed a mass in the right ventricular outflow tract with a peak systolic gradient of 52 mmHg. Contrast‐enhanced CT confirmed the presence of a lobulated mass, which extensively filled the anterior mediastinum, infiltrating the pulmonary artery trunk up to occupying the right ventricular outflow tract. CT‐guided biopsy revealed primary mediastinal B‐cellular lymphoma. The patient underwent chemotherapy, achieving complete remission of the disease at the 12‐month follow‐up, while the gradient across the pulmonary artery dropped from 52 mmHg to 14 mmHg. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:68–70, 2015